AN ANALYSIS OF ENGLISH FINAL TEST FOR THE FIRST SEMESTER OF THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 3 JOMBANG 2012/2013 (RETAIN, 2013)
Pengajaran dan tes adalah dua hal yang tidak bisa dipisahkan satu sama lain (Heaton, 1975:1). Sebuah tes memiliki sebuah tujuan yang sejalan dengan pengajaran yang telah dilakukan sebelumnya. Untuk memenuhi tujuan tersebut, tes harus memiliki karakteristik tes yang baik. Validitas dan reliabilitas adalah dua karakter utama dalam penafsiran dan penggunaan kemampuan bahasa (Bachman, 1990:24). Selain itu, untuk panduan dan perbaikan butir soal tes dibutuhkan sebuah analisis butir soal (Shakil, 2008) yang terdiri dari tingkat kesukaran dan daya beda soal. Oleh karena itu, peneliti melakukan sebuah analisis soal ujian akhir semester pertama mata pelajaran Bahasa Inggris untuk kelas XI SMAN 3 Jombang 2012/2013. Penelitian ini dilakukan untuk mengetahui validitas isi, reliabilitas, tingat kesukaran, dan daya beda soal. Peneliti menggunakan metode deskriptif quantitatif. Data penelitian terdiri dari soal, SI Bahasa Inggris kurikulum 2006, daftar nilai siswa, lembar jawaban siswa, dan kunci jawaban. Hasil penelitian menunjukkan bahwa soal ujian akhir semester pertama mata pelajaran Bahasa Inggris kelas XI SMAN 3 Jombang 2012/2013 memiliki validitas isi dengan kriteria layak dengan prosentase 70% dan reliabilitas 0.633 dengan kriteria layak. Untuk tingkat kesukaran, tes menunjukkan bahwa hampir separuh jumlah butir soal termasuk dalam kriteria mudah dengan prosentase 48%. Selain itu, untuk daya beda soal, sebagian besar butir soal termasuk kriteria tidak layak dengan prosentase 40%. Kata Kunci: validitas isi, reliabilitas, tingkat kesukaran butir soal, daya beda butir soal. Abstact Teaching and testing are so closely interrelated each other (Heaton, 1975:1). A test has a purpose which is based on the teaching before. To fulfill the purpose of the test, it should have the characteristics of good test. Validity and reliability are the two essentials to the interpretation and the use of language ability (Bachman, 1990:24). Besides, one powerful technique available to the teachers for the guidance and improvement of instruction is the test item analysis (Shakil, 2008) which consists of item difficulty and item discrimination. Based on the explanation, the researcher conducted an analysis of English final test for the first semester of eleventh grade students of SMAN 3 Jombang 2012/2013. The purpose of this study is to know the content validity, reliability, the index of difficulty and discrimination. The researcher used quantitative method within descriptive approach to describe the quality of the test based on the result of the analysis. The source of the data in this study is the English final test items; the Standar Isi of English in curriculum 2006 for the eleventh grade students for the first semester; the students’ scores and answer sheets, and the answers’ key. The result of the study leads the researcher to some conclusions that the English final test for the first semester of the eleventh grade students of SMAN 3 Jombang 2012/2013 has moderate content validity with the percentage of 70% and moderate reliability with the coefficient of 0.633. For the index of difficulty, the test shows 48% of the test items are considered as easy items. Besides, for the index of discrimination, most of the test items are poor items with the percentage of 40% because they cannot differentiate between the students who got higher and lower scores. Keywords: content validity, reliability, index of difficulty, index of discrimination.